Legal Certainty in Land Rights Acquisition in Indonesia’s National Land Law - Widiyono, Try; Khan, Md Zubair Kasem (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2023)
Acquisition of land rights has been a protracted issue due to the complexity of land laws and regulations in Indonesia. This situation often leads to illegal land disputes and conflicts. This research investigated the aspect of legal certainty in land rights based on Indonesian laws and regulations. This study focused on the aspects of legal certainty in several laws and regulations related to land rights and examined the implications of the Law on Land Acquisition and Government Regulations (PP) of 2021 concerning Management Rights, Land Rights, Flat Units, and Land Registration. The research methods involved a qualitative approach with a normative and juridical approach. The research results highlight significant progress in recent regulations, such as the Perppu Cipta Kerja 2022 and PP 2021 concerning Management Rights, Land Rights, Flat Units, and Land Registration, regarding more efficient and transparent procedures in providing legal certainty in obtaining the rights above ground. This finding implies the need for continuous improvement to strengthen legal certainty and to protect the rights of all parties. This research emphasizes the importance of harmonizing laws and regulations to create a conducive environment for the responsible and sustainable acquisition of land rights in Indonesia.